Exploring Novel Non-Operative Treatments for Osteoarthritis: An Examination of Innovative Therapies - Bakuła, Piotr Robert; Jałocha, Kamila; Zygadło, Joanna (Quality in Sport, 2025)
Osteoarthritis (OA) is a prevalent degenerative joint disease that significantly impacts the quality of life of millions worldwide, particularly the elderly. While conventional non-surgical treatments, such as NSAIDs, intra-articular injections, and physical therapy, provide symptomatic relief, their long-term efficacy and safety remain limited. Recent advancements in understanding OA pathophysiology have spurred the development of innovative therapeutic strategies targeting disease progression. This review examines emerging pharmacological and regenerative approaches, including disease-modifying osteoarthritis drugs (DMOADs), biologics, and cell-based therapies. Cutting-edge technologies such as RNA interference, CRISPR/Cas9, and advanced regenerative medicine are also explored for their potential to revolutionize OA management. Additionally, the integration of novel therapies with traditional interventions is discussed, highlighting opportunities for a more personalized, multimodal approach to OA care. Despite significant progress, challenges such as translational hurdles, cost barriers, and long-term efficacy require further investigation. This review emphasizes the transformative potential of emerging therapies in addressing the unmet needs of OA patients and shaping future treatment paradigms.